Impact of Remote Working Environment on Employee Motivation, Engagement, and Job Satisfaction: A Study of Service Sector from UAE - Jawabri, Adnan; Alarmoti, Ayman; Rehman, Waheedur (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">With the advancement in technologies and the outbreak of COVID-19 pandemic, significant changes have begun to take place in businesses, causing jobs to move from workplaces to homes indefinitely. For some, the transition from office to work was simple, while for others, juggling family and work has become a roller-coaster ride of emotions. Not all remote employees can sustain their remote working due to reduction in employee productivity and engagement. Targeting this aspect, the study focuses on examining the impact of remote working on employee motivation, engagement, and job satisfaction in case of UAE service sector. The empirical examination of 316 employee’s perception shows that remote working has a positive as well as negative impact on employee motivation, engagement, and job satisfaction. To sustain in a competitive environment, it is essential to mitigate the shortcomings and create a motivating working environment for employees.